Simulation Studies on Switching Table based DTC and Fuzzy Rule based DTC for Three-Phase Squirrel Cage Induction Motor - Tripathy, P. R.; Panigrahi, B. P. (Engineering, Technology & Applied Science Research, 2012)
This paper describes a study of Switching Table Direct Torque Control (ST-DTC) and Fuzzy Rule based Direct Torque Control (FR-DTC) in case of a three phase induction motor. The hysteresis band and the switching table used in the ST-DTC scheme have been replaced by a Fuzzy Rule based controller in the FR-DTC. Results show that the FR-DTC method provides better transient performance compared to the ST-DTC method.